2016
DOI: 10.1021/acs.nanolett.6b00888
|View full text |Cite
|
Sign up to set email alerts
|

Gap States at Low-Angle Grain Boundaries in Monolayer Tungsten Diselenide

Abstract: Two-dimensional (2D) transition metal dichalcogenides (TMDs) have revealed many novel properties of interest to future device applications. In particular, the presence of grain boundaries (GBs) can significantly influence the material properties of 2D TMDs. However, direct characterization of the electronic properties of the GB defects at the atomic scale remains extremely challenging. In this study, we employ scanning tunneling microscopy and spectroscopy to investigate the atomic and electronic structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 42 publications
4
59
0
Order By: Relevance
“…[13,14,25] Moreover, the electronic structure of the GBs were studied using scanning tunneling microscopy (STM). [26,27] Importantly, mirror twin boundaries (MTBs) with particular atomic structures between regions with 60° relative orientation have been repeatedly reported. [28][29][30] These were observed either upon flake merging, inside grains to accommodate for the nonstoichiometry, or produced a posteriori by electron-beam or thermal-annealing treatments.…”
Section: Progress Reportmentioning
confidence: 99%
“…[13,14,25] Moreover, the electronic structure of the GBs were studied using scanning tunneling microscopy (STM). [26,27] Importantly, mirror twin boundaries (MTBs) with particular atomic structures between regions with 60° relative orientation have been repeatedly reported. [28][29][30] These were observed either upon flake merging, inside grains to accommodate for the nonstoichiometry, or produced a posteriori by electron-beam or thermal-annealing treatments.…”
Section: Progress Reportmentioning
confidence: 99%
“…GB and edges always exhibit PL signals different from that at the crystal center. These nonuniformities can be attributed to localized states, doping, and strain [57,78,119,120]. Figure 10A and B shows PL and Raman images of monolayer MoS 2 after thermal annealing.…”
Section: Edge and Grain Boundary In Tmds Probed By Pl Spectroscopymentioning
confidence: 99%
“…Scanning transmission electron microscope studies on GBs in 2D TMDs have found that a variety of non-6-membered rings (4-, 5-, 7-, and 8-membered rings) together with strained 6-membered rings are present at GBs with different misorientation angles [120]. Density functional theory (DFT) calculation has shown that all these non-6-membered dislocation cores can induce deep gap states [120].…”
Section: Edge and Grain Boundary In Tmds Probed By Pl Spectroscopymentioning
confidence: 99%
“…C60F48 is selected as a model molecule because it is a molecular acceptor [32] with applications in lithium batteries [33,34], electronic devices [35][36][37] and so on [38,39]. WSe2 represents as a prototypical 2D-TMD semiconductor with a high photon quantum yield [30,31,40,41]. As revealed by STM investigations, a liquid-solid surface phase transition is observed from a loose-packed liquid phase at dilute coverage to a closed-packed solid phase at high coverage.…”
Section: Introductionmentioning
confidence: 99%